Pembangunan Perisian Pembelajaran Berbantukan Komputer (PBK) Bagi Kursus Perdagangan Jual Beli Mata Wang Kripto Dogecoin menggunakan Pergerakan Purata Mudah - Mohd Norihan, Muhammad Naseem Khan; Mohd Saupi, Muhamad Nor Aiman; Mohammad Nazri, Iffah Ayunie; Surip, Miswan (Multidisciplinary Applied Research and Innovation, 2022)
This application software focuses on Dogecoin cryptocurrency trading on Binance Exchanger. This application is also a computer -assisted learning software (CALL) which will make it easier for beginners to learn to trade cryptocurrencies easily and effectively. As we all know, digital currency in this age of technological sophistication is gaining public attention because it will provide multiplied profits to the trader. This PBK integrates multimedia-related elements such as text, video, graphics, and quizzes to attract interest and make it easier for users to use our PBK application. This application is dedicated to the unemployed, university students and the community aged 18 and above. This PBK strategy through tutorials and learning theories is more constructivist in the foundation of this application development. This PBK software is interactive for the purpose of learning cryptocurrency trading by using simple moving averages more easily and effectively and quickly understood. This PBK software is designed and developed using the ADDIE Model methodology applied in this software to focus on the use of mobile movement more easily in order to reap multiple profits while trading. The evaluation and feedback on the application that we received from the target group is very encouraging and they are satisfied with the results of this product and hope that improvements to our product will always be made in the future.